Avaliação dos impactos do ensino remoto emergencial nos processos de alfabetização e letramento de crianças no período pós-pandêmico em Iguatu-CE - Silva, Maria Aurinólia Barreto (2024)
The COVID-19 pandemic, decreed by the World Health Organization in March 2020, has required educational institutions to migrate their educational activities from face- to-face to virtual through the adoption of Emergency Remote Education (ERE). Children's literacy and literacy have been directly impacted by this scenario, as their audience, made up of children at an important stage of human development, lack the maturity to deal with digital technologies compared to adolescents and adults. Given this reality, this dissertation chose the following research question: How did the literacy and literacy of children in the first year of elementary school in the public schools of the municipal network of Iguatu/CE, in 2022, who experienced Early Childhood Education, through ERE, in 2020 and 2021? In order to answer this question, the general objective was to investigate, from the teachers' point of view, how the literacy process of children enrolled in the first year of elementary school in the municipality of Iguatu-CE, from the ERE, carried out during the COVID-19 pandemic, was carried out. To this end, a qualitative-quantitative case study was carried out with 28 teachers from public primary schools in the municipality of Iguatu, Ceará, using a structured questionnaire and interviews as research tools. The data was analyzed in the light of the Context, Input, Process and Product (CIPP) model of evaluation. The data revealed that teachers perceive the post-pandemic scenario as challenging for children's literacy, as they identify several negative factors that impacted on the learning of children enrolled in Early Childhood Education during the pandemic, such as: difficulties in monitoring by families, limited or non-existent access to technological tools, demotivation due to the lack of face-to-face interaction between students and their teachers, among other factors. In addition, the research data enabled the construction of an e-book with experience reports from teachers in Iguatu/CE on the literacy process for children using ERE during the COVID-19 pandemic, in order to publicize the work carried out by these teachers in this context.